Comparation between Fibroscan and Hepatus for Detecting NAFLD in Patients with Metabolic Dysregulation - Sun, Jie-hui; Zhang, Ping-ping; Wang, Kun; Xu, Miao; Sun, Jing; Li, Li (The Indonesian Society for Digestive Endoscopy, 2024)
Background The clinical application of the innovative instantaneous elasticity and fat attenuation measurement technology, Hepatus, is currently in the evaluation stage. This study aimed to compare the detection performance of Fibroscan and Hepatus in patients with metabolic dysregulation who are